(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
Transcription and translation of material from the link: https://www.youtube.com/watch?v=LcOb83plY4c&ab_channel=JasonWBlakely done by Mirza Čerkez.